THE USING OF CAI-BASED LEARNING MEDIA IN THE FORM OF TUTORIAL VIDEO FOR THE SUBJECT USING MEASUREMENT DEVICES IN THE TENTH GRADE OF TKR SMK KARSA MULYA PALANGKA RAYA 2014/2015 - Joni; Duling, Jhonni Rentas (Jurusan Pendidikan Teknologi Dan Kejuruan, 2016)
The low students study results in the learning activity using mechanic measurement devices is a background of the problem, caused by teacher’s teaching method is still using a conventional approach which is just a verbal lecture without using computer media, it can be seen from student’s low study results. This research aims to find out the level of students’ comprehention on the subject material with the number student of 30. The research is designed in three stages which are pretest stage, learning stage, and post test stage. Data collecting method to be used are documentation, dan test method. Instruments to be used are test and questionnaire. This research is a descriptive research that had been done on the tenth grade student of TKR SMK Karsa Mulya Palangka Raya tahun ajaran 2014/2015. The student achievement level reached 83,4%. It means that learning process using tutorial video on the subject material Using mechanic measurement devices is achieved as per the achievement level criteria of learning process which is 80-100%. It can be concluded that learning model CAI (Computer Assistance Instruction) in the form of tutorial video can be used as an alternative in delivering subject material Using the mechanic measurement devices.